Cosmic ray observations at high zenith angles ... - Vrana, A (University Of Tasmania, 2023)
The thesis is the description of the design and construction of a high zenith angle telescope for the Mawson observatory, together with some discussion of results obtained. Because the new Mawson observatory installed in 1972 is a logical extension complementing the high zenith angle experiment, it was felt that inclusion of a brief description of the new observatory complex would not be out of place. l joined the Australian National Antarctic Research Expedition in 1964 as an expedition physicist. During my stay at Mawson in 1965 I became aware of the shortcomings of mains operated electronic equipment at remote stations and designed some battery operated solid state circuits to replace the former circuitry. Upon my return from Mawson I was commissioned to finalise the design of the transistorised circuitry and develop modular circuit units for the use with counter telescopes. In 1966 a joint project was proposed by the Antarctic Division and the University of Tasmania for a high zenith angle ground based ...